2018
DOI: 10.24917/25438832.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Host preferences of wood-decaying fungi of the genus Ganoderma in the urban areas of Slovakia

Abstract: Ganoderma (Basidiomycota, Polyporales) is a cosmopolitan genus with the greatest diversity in the tropics. It causes white rot of a wide range of woody plants all over the world. In Europe, 7 species of the genus Ganoderma grow: Ganoderma adspersum, G. applanatum, G. carnosum, G. lucidum, G. pfeifferi, G. resinaceum and G. valesiacum. All of them also occur in Slovakia. The aim of the present study was to identify the presence of Ganoderma species in the urban areas of Slovakia and to find out their host prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…5 and 7), which is also confirmed by the research of Watson and Green [2011]. On this basis, it is therefore concluded that the fungus is clearly more a parasite than a saprotroph, which is also confirmed by the research of Beck et al [2018]. A critical view should be taken of the observations of Lonsdale [1999] and Beck et al [2018], who notice the morphological similarity between G. resinaceum and G. lucidum.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…5 and 7), which is also confirmed by the research of Watson and Green [2011]. On this basis, it is therefore concluded that the fungus is clearly more a parasite than a saprotroph, which is also confirmed by the research of Beck et al [2018]. A critical view should be taken of the observations of Lonsdale [1999] and Beck et al [2018], who notice the morphological similarity between G. resinaceum and G. lucidum.…”
Section: Resultssupporting
confidence: 60%
“…The GRAJ register of protected Fungi lists the species only at two sites in Poland: in Kraków and Poznań [Snowarski 2020]. Both sites are related to green areas rather than forest stands, which is also consistent with the research of Beck et al [2018], who indicate the presence of the fungus in parks and gardens, and in warmer regions, also in forests. The observations of Sokół et al [1986] and Wojewoda [1999] of the species in Silesia.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…It grows on a wide range of living and dying angiosperms trees (it can form basidiomata even several years after the death of the host), and rarer on conifers (Table 1), (Figure 1). In Europe, it is found most often in the southern and western parts [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Wood decay polypore fungi of the genus Ganoderma, some species of which have long been cultivated used in traditional oriental medicine [1][2][3][4], are widespread in warm regions and are often found in parks and gardens [5]. These fungi have thick, corky fruiting bodies (basidiocarps), which are capable of growing on affected dead or living trees at the site of injury and causing white rot.…”
Section: Introductionmentioning
confidence: 99%